A relação do pensamento crítico do serviço social com o feminismo no Brasil - (:unkn) unknown (Universidade Federal do Pampa, 2021)
This work is about Social Service, Women's Rights Movement and the issues involving gender and violence against women from the society. This study has the following goal: analyze the influence of Brazilian Women's Rights Movement, beginning at the Reconceptualization of Social Service, in order to build critical knowledge for the Social Service so as to understand the debate and strategies of this social and political movent for the Social Worker’s job. To deal with this theme the following research problem was proposed: in which way has Social Service, from the Reconceptualization movement, articulated the critical knowledge of possible influences of the Women’s Rights Movent in Brazil. This work uses the following methodological procedures: critical dialetical method and bibliographic research both qualitative and exploratory. To obtain the samples for the subjects of Social Work, gender and feminism, the Scielo Platform was used. To organize bibliographic data collected during the analysis, records were used for notes and documentation. That said, it was found that the bond between Social Work and the Women’s Rights movement started with the Reconceptualization movement where the Social Worker profession adopted a critical thinking based on the Marxian theory. This evolution aided the first contacts of the Social Worker profession with the social movements and the working class.
Keywords: Serviço Social; Feminismo; Identidade de gênero; Social services; Feminism; CNPQ::CIENCIAS SOCIAIS APLICADAS